Preparation and application of a zr-based metal-organic framework anchoring metal diatom

CN118892867BActive Publication Date: 2026-10-30DONGGUAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410948326.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-16
Publication Date
2026-10-30
Estimated Expiration
2044-07-16

AI Technical Summary

Technical Problem

[0010]综上所述,结合过硫酸盐活化高级氧化技术存在的缺陷,以及传统降解技术难以降解PFAS污染物等问题,本发明研究出一种锚定双单原子的Zr基金属有机框架来活化过硫酸盐,以提高羟基自由基、硫酸根自由基生成效率及高效选择性降解PFAS污染物的方法;有益于提高含氟有机污染物废水的净化效率,同时这项研究为调控催化剂电子结构,控制催化剂金属不饱和位点的形成开辟了新途径,并为设计高效光催化剂提供了指导,对开发新的锚定双单原子的MOFs光催化氧化类芬顿系统来降解污染物有一定的启示

Benefits of technology

[0028]与现有技术相比,本发明所达到的有益效果是:过硫酸盐-高级氧化技术是一类处理持久性有机污染物的有效技术;而活化过硫酸盐(PDS)是处理含氟有机污染物废水的主要材料,通过产生硫酸根自由基(SO4·-)能够高效降解污染物,但目前的活化技术存在难于重复,已造成污染等问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118892867B_ABST
    Figure CN118892867B_ABST
Patent Text Reader

Abstract

The application relates to the field of metal organic frameworks, and particularly discloses preparation and application of a Zr-based metal organic framework anchoring metal double atoms. The application comprises the following operation steps: vacuum activation of UiO-66-NH2 to obtain activated UiO-66-NH2; placing the activated UiO-66-NH2 in a DMF-water solution, adding silver solution and cobalt solution drop by drop, uniformly ultrasonic dispersing to obtain a mixture; placing the mixture under irradiation of a high-pressure mercury lamp, washing, centrifuging and drying to obtain the Zr-based metal organic framework anchoring metal double atoms. The Zr-based metal organic framework anchoring metal double atoms, an oxidizing agent and a UV light source are combined to form a photocatalytic degradation system, which is used for degrading fluorine-containing organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal-organic framework technology, specifically to the preparation and application of a Zr-based metal-organic framework anchored to metal diatoms. Background Technology

[0002] Perfluorinated and polyfluoroalkyl substances (PFAS) are a class of substances containing at least one perfluorinated methyl group (CF3). 3- ) or methylene (-CF 2- Non-natural, artificially synthesized organic compounds containing no H / C / Br / I atoms. As of September 2023, the PubChem database records over 7 million per- and polyfluoroalkyl substances (PFAS) and over 21 million fluorinated compounds, including common perfluorocarboxylic acids (PFCA), perfluorosulfonates (PFOS), and perfluoroether carboxylic acids (PFECA).

[0003] Because of their excellent thermal stability, chemical stability, high surface activity, and hydrophobic and oleophobic properties, PFAS are widely used in industrial and daily life. Compared with non-fluorinated persistent organic pollutants, PFAS are more resistant to environmental and targeted degradation and can exist stably in the natural environment for a long time. Due to their unique environmental persistence and bioaccumulation, they have a profound impact on drinking water, surface water, livestock and agricultural products around the world.

[0004] Currently, conventional treatment processes used in traditional wastewater treatment plants are unable to effectively degrade these pollutants, resulting in the continuous release of large amounts of PFAS into the environment. Therefore, it is necessary to develop efficient removal technologies to address the problem of PFAS pollution in water bodies.

[0005] In recent years, advanced oxidation technologies (AOs) have been widely used in the deep treatment of organic wastewater and drinking water. OAOs originated from the emergence of hydroxyl radicals (·OH) and have developed rapidly. Due to the extreme stability and recalcitrant nature of some organic pollutants, technologies capable of generating more reactive sulfate radicals (SO4) have emerged. ·- The persulfate-advanced oxidation technology; compared to ·OH, the strongly oxidizing species SO42- ·- With higher redox potential, longer half-life, and milder reaction conditions, it can effectively remove persistent organic pollutants from the environment.

[0006] Because persulfate-advanced oxidation technology requires external energy input to break the O and O bonds and generate a large amount of SO4. ·- ·OH participates in the degradation process of pollutants; however, homogeneous PDS (persulfate) activation is difficult to replicate and can cause pollution, so research on heterogeneous methods has gradually become the mainstream.

[0007] Among numerous heterogeneous PDS (persulfate) activation methods, the photocatalytically assisted PDS activation reaction mediated by photocatalyst / light / PDS can achieve synergistic coupling of photocatalysis and Fenton-like reactions, maximizing the utilization of both the photocatalyst and PDS. In photocatalytic advanced oxidation processes, the performance design of the photocatalyst determines the activation efficiency of the photocatalytic system for PDS and the degradation efficiency for PFOA. Therefore, there is an urgent need to find a new photocatalyst for efficient catalysis of PDS.

[0008] In recent years, single-atom catalysts have attracted widespread attention in the field of photocatalysis due to their high atomic utilization, tunable active sites, and excellent catalytic performance, and they possess enormous research potential for environmental applications. Using appropriate synthesis methods and procedures, single-atom loadings with ultra-high atomic density (5–15 atoms per square nanometer) and extremely close site distances (0.2–0.5 nm) can be achieved on support surfaces.

[0009] Among them, the structure and surface groups of MOF materials can be flexibly tailored and modified, and they have a large specific surface area and high chemical stability, which greatly facilitates the precise control of the microenvironment at the atomic scale. They are ideal models for studying the microenvironment control in electrocatalysis and photocatalysis processes, and can serve as ideal substrate materials for single-atom catalysts.

[0010] In summary, considering the shortcomings of persulfate-activated advanced oxidation technology and the difficulty of traditional degradation technologies in degrading PFAS pollutants, this invention presents a method for activating persulfate using a Zr-based metal-organic framework anchored to two single atoms, thereby improving the generation efficiency of hydroxyl radicals and sulfate radicals and achieving efficient and selective degradation of PFAS pollutants. This method is beneficial for improving the purification efficiency of fluoride-containing organic pollutant wastewater. Furthermore, this research opens up new avenues for regulating the electronic structure of catalysts and controlling the formation of unsaturated sites on catalyst metals, and provides guidance for designing highly efficient photocatalysts. It also offers insights for developing novel Fenton-like photocatalytic oxidation systems anchored to two single atoms for pollutant degradation. Summary of the Invention

[0011] The purpose of this invention is to provide a method for preparing and applying a Zr-based metal-organic framework anchored to metal diatoms, in order to solve the problems mentioned in the background art.

[0012] The preparation of a Zr-based metal-organic framework anchored to metal diatoms includes the following steps:

[0013] S1: Vacuum activation of UiO-66-NH2 yields activated UiO-66-NH2;

[0014] S2: Place the activated UiO-66-NH2 in a DMF-water solution, add silver solution and cobalt solution dropwise, and ultrasonically disperse until uniform to obtain a mixture;

[0015] S3: Irradiate the mixture under a high-pressure mercury lamp, wash, centrifuge, and dry to obtain a Zr-based metal-organic framework anchored to metal diatoms.

[0016] In a more optimized form, the Zr-based metal-organic framework anchored to metal diatoms comprises 98wt%–99wt% UiO-66-NH2, 0.5wt%–1wt% Ag atoms, and 0.5wt%–1wt% Co atoms.

[0017] More preferably, the percentage content of UiO-66-NH2 is typically, but not limited to, 98%, 98.5%, or 99%, the percentage content of Ag atoms is typically, but not limited to, 0.5%, 0.75%, or 1%, and the percentage content of Co atoms is typically, but not limited to, 0.5%, 0.75%, or 1%.

[0018] More optimally, the vacuum activation temperature is 110–130°C, and the vacuum activation time is 10–14 hours.

[0019] More preferably, the vacuum activation temperature is typically, but not limited to, 110°C, 115°C, 120°C, 125°C, or 130°C, and the vacuum activation time is typically, but not limited to, 10 hours, 11 hours, 12 hours, 13 hours, or 14 hours.

[0020] Ideally, the concentration of the silver salt solution is 10 g / L, the concentration of the cobalt salt solution is 10 g / L, and the DMF accounts for 10 wt% of the DMF-water solution.

[0021] Ideally, the high-pressure mercury lamp has a power of 400-600W and an irradiation time of 1-2 hours.

[0022] The more optimized preparation of the Zr-based metal-organic framework anchored with metal diatoms includes the following steps: (1) Disperse activated UiO-66-NH2 in 60 mL of a mixed solution of deionized water and DMF (deionized water: DMF = 9:1), slowly add 0.141 mL of silver nitrate (10 g / L) and 0.445 mL of cobalt nitrate solution (10 g / L), and ultrasonically disperse evenly to obtain a mixture; (2) Fix a 500 W high-pressure mercury lamp above the mixture, with the solution surface of the mixture 20 cm away from the high-pressure mercury lamp, and continuously irradiate with the high-pressure mercury lamp for 1 hour under stirring conditions, then place it in a centrifuge and wash it multiple times with methanol and water, set the speed to 12000 r / min, centrifuge for 5 minutes, collect the product and place it in a vacuum drying oven, set the drying temperature to 60 °C, and the drying time to 12 hours to obtain the Zr-based metal-organic framework anchored with metal diatoms.

[0023] A more optimized preparation method for UiO-66-NH2 is as follows: ZrCl4 and 2-aminoterephthalic acid are added to DMF and mixed evenly, acetic acid and triethylamine are added to obtain mixture A; mixture A is subjected to hydrothermal reaction at 120°C for 45-50 hours, cooled to room temperature, purified, and dried to obtain UiO-66-NH2.

[0024] In a more optimized form, the raw materials for mixture A include the following components: 2 mmol ZrCl4, 2 mmol 2-aminoterephthalic acid, 100 mL DMF, 10 mL acetic acid, and 0.2 mL triethylamine.

[0025] A more optimized preparation of UiO-66-NH2 includes the following steps: Weigh 2 mmol ZrCl4 and 2 mmol 2-aminoterephthalic acid, and mix them in 100 mL of water. The mixture was completely dissolved in DMF. Then, 10 mL of acetic acid and 0.2 mL of triethylamine were slowly added. The resulting mixture was poured into a Teflon-lined steel autoclave and placed in an electrically heated drying oven. The temperature was typically, but not limited to, 110°C, 120°C, and 130°C, and the time was typically, but not limited to, 36 hours, 48 ​​hours, and 60 hours. After the reaction was complete, the Teflon liner was removed, cooled to room temperature, and then placed in a centrifuge. The speed was typically, but not limited to, 9000–12000 r / min, and the centrifugation time was typically, but not limited to, 3 minutes, 4 minutes, 5 minutes, 6 minutes, and 7 minutes. After the reaction was complete, the mixture was washed three times with methanol and deionized water, and then placed in an electrically heated drying oven. The drying temperature was set to 60°C, and the drying time was typically, but not limited to, 10 hours, 11 hours, 12 hours, 13 hours, and 14 hours to obtain UiO-66-NH2.

[0026] An optimized application of a Zr-based metal-organic framework anchored to metal diatoms is described, wherein the Zr-based metal-organic framework anchored to metal diatoms serves as a photocatalyst, which, together with an oxidant and an ultraviolet light source, forms a photocatalytic degradation system for treating wastewater containing fluorine organic pollutants.

[0027] In a more optimized configuration, the fluorinated organic pollutant in the wastewater is perfluorooctanoic acid (PFOA), the oxidant is persulfate, and the power of the ultraviolet light source is 300W.

[0028] Compared with existing technologies, the beneficial effects achieved by this invention are as follows: persulfate-advanced oxidation technology is an effective technology for treating persistent organic pollutants; and activated persulfate (PDS) is a major material for treating wastewater containing fluoride organic pollutants, by generating sulfate free radicals (SO4). ·- It can efficiently degrade pollutants, but current activation technologies are difficult to replicate and have caused pollution problems.

[0029] Therefore, this invention designs a photocatalyst to utilize a photocatalyst / light / PDS-mediated photoelectrocatalytic assisted PDS activation reaction; the unsaturated sites formed by metal single atoms have a promoting chemical confinement effect, effectively attracting PFAS molecules and PDS, thus enhancing SO4 activation. ·- The intermolecular forces between the source material and PFAS molecules promote the degradation of PFAS.

[0030] Anchoring a dual-single-atom AgCo metal-organic framework as a photocatalyst can effectively modulate the catalyst's electronic structure, improve the transfer efficiency of photogenerated carriers, and transfer delocalized photogenerated electrons to Ag sites, forming electron-rich Ag active sites. This lowers the energy barrier for H2O dissociation and effectively enables photogenerated electrons (electrons) to be excited on the surface. - ) and photogenerated holes h + Co reacts with H₂O to generate ·OH, and the single-atom Co and Ag form a heterogeneous phase point. The resulting neighboring electron synergistic effect is beneficial to the electron transfer process of PMS, accelerating the redox cycle of cobalt and jointly promoting the photocatalytic activation of PMS, effectively activating PMS to generate SO₄²⁻. ·- . Attached Figure Description

[0031] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:

[0032] Figure 1 This is a scanning electron microscope image of the Zr-based metal-organic framework UiO-66-NH2 in Example 1.

[0033] Figure 2This is a 300nm scanning electron microscope image of the Zr-based metal-organic framework anchored with two single-atom AgCo atoms in Example 2.

[0034] Figure 3 This is a 500nm scanning electron microscope image of the Zr-based metal-organic framework anchored with two single-atom AgCo atoms in Example 2.

[0035] Figure 4 This is a schematic diagram of the heterogeneous degradation of fluoride-containing organic wastewater by a Zr-based metal-organic framework / photo / PDS anchored to two single-atom AgCo atoms. Detailed Implementation

[0036] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] It should be noted that there are no special restrictions on the manufacturers of the raw materials involved in this invention. Exemplary examples include: 2-aminoterephthalic acid (CAS number 10312-55-7), zirconium tetrachloride (ZrCl4) (CAS number 10026-11-6), triethylamine (CAS number 121-44-8), silver nitrate (CAS number 7761-88-8), and cobalt nitrate (CAS number 10026-22-9).

[0038] Example 1: Weigh 2 mmol ZrCl4 and 2 mmol 2-aminoterephthalic acid, and completely dissolve them in 100 mL DMF. Then, slowly add 10 mL acetic acid and 0.2 mL triethylamine. Pour the resulting mixture into a Teflon-lined steel autoclave and place it in an electrically heated drying oven. Set the temperature to 120 °C and the time to 48 hours. After the reaction is complete, cool it at room temperature and then place it in a centrifuge to wash it multiple times with methanol and water. Set the speed to 12000 r / min and centrifuge for 5 minutes. Collect the product and place it in a drying oven. Set the drying temperature to 60 °C and the drying time to 12 hours to obtain UiO-66-NH2 (Zr-based metal-organic framework).

[0039] Example 2: UiO-66-NH2 was placed in a vacuum drying oven at 120°C for 12 hours. The activated UiO-66-NH2 was dispersed in 60 mL of a mixed solution of deionized water and DMF (deionized water:DMF = 9:1). 0.141 mL of silver nitrate (10 g / L) and 0.445 mL of cobalt nitrate solution (10 g / L) were slowly added dropwise to the dispersion. The mixture was ultrasonically dispersed until homogeneous. A 500W high-pressure mercury lamp was fixed above the UiO-66-NH2 dispersion, with the solution surface 20 cm away from the lamp. The mixture was continuously irradiated with the high-pressure mercury lamp for 1 hour under stirring. The product was then centrifuged and washed multiple times with methanol and water at 12000 r / min for 5 minutes. The collected product was placed in a vacuum drying oven at 60°C for 12 hours to obtain a Zr-based metal-organic framework (AgCo SAs UiO-66-NH2) anchored to two metal atoms.

[0040] Performance Test 1: Using a 300W mercury lamp as the ultraviolet light source, 5 mg of PFOA was added to both the control group without catalyst and the UiO-66-NH2 and AgCo SAs (UiO-66-NH2 as catalyst) from Examples 1-2. The conditions were set as follows: PFOA concentration 10 mg / L, persulfate amount 1 mM, reaction solution volume 50 mL, and degradation times of 10, 30, 60, 240, and 480 minutes. The degradation rate of PFOA was measured, and the data obtained were the average values ​​of the three degradation experiments, as shown in Table 1.

[0041] Degradation rate in 10 minutes 1.2% 5.1% 10.4% Degradation rate in 30 minutes 3.9% 12.3% 27.3% Degradation rate in 60 minutes 5.2% 29.4% 50.5% Degradation rate in 240 minutes 17.4% 52.1% 73.9% Degradation rate in 480 minutes 34.1% 71.9% 91.6%

[0042] Table 1

[0043] Conclusion: Comparing Examples 1 and 2, it can be seen that the AgCo SAs UiO-66-NH2 prepared in Example 2 of this invention has a much higher photocatalytic removal rate of PFOA than the control group and Example 1 under the condition of using a 300W mercury lamp as the light source.

[0044] Performance Test 2: AgCo SAs UiO-66-NH2 was added at 5 mg per tonne to PDS (0.5 mM, 1 mM, 1.5 mM), and the current density for each of the three groups was set to 10 mA·cm⁻¹. -2 15mA·cm -2 20mA·cm -2 Other settings remained the same as in Experiment 1, and the degradation rate of PFOA was measured. See Table 2 for details.

[0045]

[0046]

[0047] Table 2

[0048] Conclusion: Comparison of 0.5 mM PDS and 10 mA·cm -2 Current density, found to be 1 mM PDS and 15 mA·cm -2 The degradation rate of PFOA showed a sharp increase under different current densities. This indicates that AgCo SAs UiO-66-NH2, at a PDS concentration of approximately 1 mM, can achieve a degradation rate of PFOA at 15 mA·cm⁻¹. -2 The current density can fully utilize the PDS to generate a large number of hydroxyl radicals and sulfate radicals, which greatly improves the degradation rate of PFOA.

[0049] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0050] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a Zr-based metal-organic framework anchored to metal diatoms, characterized in that: The following steps are included: S1: Vacuum activation of UiO-66-NH2 yields activated UiO-66-NH2; S2: Place the activated UiO-66-NH2 in a DMF-water solution, add silver solution and cobalt solution dropwise, and ultrasonically disperse until uniform to obtain a mixture; S3: Irradiate the mixture under a high-pressure mercury lamp, wash, centrifuge, and dry to obtain a Zr-based metal-organic framework anchored to metal diatoms; The Zr-based metal-organic framework anchored to metal diatoms comprises 98wt%–99wt% UiO-66-NH2, 0.5wt%–1wt% Ag atoms, and 0.5wt%–1wt% Co atoms; The preparation of UiO-66-NH2 is as follows: ZrCl4 and 2-aminoterephthalic acid are added to DMF and mixed evenly, acetic acid and triethylamine are added to obtain mixture A; mixture A is subjected to hydrothermal reaction at 120℃ for 45-50 hours, cooled to room temperature, purified, and dried to obtain UiO-66-NH2.

2. The method for preparing a Zr-based metal-organic framework anchored to metal diatoms according to claim 1, characterized in that: The vacuum activation temperature is 110–130°C, and the vacuum activation time is 10–14 hours.

3. The method for preparing a Zr-based metal-organic framework anchored to metal diatoms according to claim 1, characterized in that: The concentration of the silver solution is 10 g / L, the concentration of the cobalt solution is 10 g / L, and the DMF content in the DMF-water solution is 10 wt%.

4. The method for preparing a Zr-based metal-organic framework anchored to metal diatoms according to claim 1, characterized in that: The high-pressure mercury lamp has a power of 400-600W and an irradiation time of 1-2 hours.

5. The method for preparing a Zr-based metal-organic framework anchored to metal diatoms according to claim 1, characterized in that: The raw materials of the mixture A include the following components: 2 mmol ZrCl4, 2 mmol 2-aminoterephthalic acid, 100 mL LDMF, 10 mL acetic acid, and 0.2 mL triethylamine.

6. An application of a Zr-based metal-organic framework anchored to metal diatoms, characterized in that: The Zr-based metal-organic framework with anchored metal diatoms prepared by the method according to any one of claims 1 to 5 is used as a photocatalyst. It, together with an oxidant and an ultraviolet light source, forms a photocatalytic degradation system to treat wastewater containing fluorine organic pollutants.

7. The application of the Zr-based metal-organic framework anchored to metal diatoms according to claim 6, characterized in that: The fluorinated organic pollutant in the wastewater is perfluorooctanoic acid (PFOA), the oxidant is persulfate, and the power of the ultraviolet light source is 300W.

Citation Information

Patent Citations

  • Car coupler

    CA121448A

  • Preparation method and application of UiO-66 defect-induced monatomic supported catalyst

    CN113769789A

  • Alloy structure modified metal organic framework material as well as preparation method and application thereof

    CN116903872A